THE ANALYSIS OF INTENTION TO BUY: AN EXTENDED THEORY OF PLANNED BEHAVIOR - Danu Gilang Pinasthika; Agus Suroso; Siti Zulaikha Wulandari (IAIN Surakarta, 2021)
This research is aimed to test an empirical study on UNSOED Press. The study took the title: